Going offshore or better staying in? Spatial relocation strategies and their impact on firm innovativeness. Issue 12 (12th July 2017) - Kreutzer, Fabian; Mitze, Timo
ABSTRACT: We analyse the short- to mid-run effects of spatial relocation strategies on firm innovativeness and productivity growth. Using conditional difference-in-difference estimation with multiple treatments, we find for a sample of German firms in 1999–2013 that offshoring has a statistically significant negative impact on the firms' innovation activity and productivity growth vis-à-vis nonrelocating comparison firms. In contrast, we find a positive link between domestic relocation activities and the firms' propensity to introduce a product innovation. Firms should thus carefully account for potentially distorting performance effects when deciding about the spatial scale of relocation strategies in the short to mid-run.